2021
DOI: 10.1007/s40262-021-01072-4
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of a Virtual Population of Children with Obesity for Physiologically Based Pharmacokinetic Modeling

Abstract: Background and Objective While one in five children in the USA are now obese, and more than three-quarters receive at least one drug during childhood, there is limited dosing guidance for this vulnerable patient population. Physiologically based pharmacokinetic modeling can bridge the gap in the understanding of how pharmacokinetics, including drug distribution and clearance, changes with obesity by incorporating known obesity-related physiological changes in children. The objective of this study was to develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
74
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 25 publications
(81 citation statements)
references
References 45 publications
(72 reference statements)
7
74
0
Order By: Relevance
“…V ss can be defined using the equation below: where V plasma is plasma volume, V tissue is tissue water volume, f u,p is fraction unbound in plasma, and f u,t is fraction unbound in tissue. Increased V plasma and V tissue (given more distribution space) can increase cardiac output during obesity ( Vasan, 2003 ; Colles et al, 2006 ; Gerhart et al, 2021 ), potentially increasing the V ss on an absolute scale. However, the extent of increase in V ss is also dependent on the drug binding to plasma protein (that determines ) as well as to the tissue components (that determines ), which are potentially altered due to altered composition during obesity.…”
Section: Physiological Considerationsmentioning
confidence: 99%
See 4 more Smart Citations
“…V ss can be defined using the equation below: where V plasma is plasma volume, V tissue is tissue water volume, f u,p is fraction unbound in plasma, and f u,t is fraction unbound in tissue. Increased V plasma and V tissue (given more distribution space) can increase cardiac output during obesity ( Vasan, 2003 ; Colles et al, 2006 ; Gerhart et al, 2021 ), potentially increasing the V ss on an absolute scale. However, the extent of increase in V ss is also dependent on the drug binding to plasma protein (that determines ) as well as to the tissue components (that determines ), which are potentially altered due to altered composition during obesity.…”
Section: Physiological Considerationsmentioning
confidence: 99%
“…However, the extent of increase in V ss is also dependent on the drug binding to plasma protein (that determines ) as well as to the tissue components (that determines ), which are potentially altered due to altered composition during obesity. While studies have shown that plasma composition with respect to serum albumin and hematocrit are largely unaffected by obesity, it changes with respect to α 1-acid glycoprotein (AAG), which increases approximately 2-fold with obesity in adults ( Benedek et al, 1983 , 1984 ; Blouin et al, 1987 ; Gerhart et al, 2021 ). However, this increase in AAG has not yet been identified in pediatric populations with obesity due to limited studies ( Gerhart et al, 2021 ).…”
Section: Physiological Considerationsmentioning
confidence: 99%
See 3 more Smart Citations